(untitled) (Bioresearch Communications, 2023)
Bangladesh is a land of medicinal plants. Terminalia catappa is an important medicinal plant of Bangladesh which is used for various pharmacological and biological activities like hepatoprotective, antioxidant, anti-fertility, antidiabetic, anticoagulant and antimicrobial. The coarsely powder dried stem bark sample of T. catappa was extracted by the solvent CHCl3. The concentrated extract was then fractionated by flash column chromatography using petroleum ether, ethyl acetate and methanol as solvents respectively. The column fraction was further fractionated with void liquid chromatography. Repeated preparative thin layer chromatography of selective fractions resulted in the isolation of two compounds which were identified as a triterpenoid, taraxerol (1) and a steroid, Stigmastane-3, 6-diol (2). The structure of these compounds were elucidated by 1H NMR spectroscopy and by comparison with reported values. This is the first report of the isolation of these compounds from this plant. The different extracts also showed significant antibacterial activity against gram positive and gram negative bacteria. The methanol extract did not show significant activity. The antifungal activity of different extract of T. catappa demonstrated promising zone of inhibition except Saccharomyces cerevecae. In the brine shrimp lethality bioassay, the extract of T. catappa exhibited a significant cytotoxic activity. The LC50 value of CHCl3 soluble extract was found to be 1.55 μg/ml. T. catappa was also reported to have free radical scavenging activity with IC50 value of 255.0 μg/ml. Since this plant demonstrated a number of promising pharmacological biological activities, so it can be a good source of natural medicine. Bioresearch Commu. 9(2): 1310-1319, 2023 (July)